Roughness effect on velocity distribution through rock fracture - Javadi, M.; Sharifzadeh, Mostafa; Shahriar, K.; Mehrjooei, M. (Sharif University, 2011)
Fractures in rock mass are the main flow paths and introduce as the most important attribute in rock mass hydraulic behavior. Hydraulic properties of rock mass are important in civil, mining, and environmental activities such as isolation of hazardous and nuclear waste, petroleum and geothermal energy. In this paper, turbulent flow through an artificial three-dimensional rock fracture was simulated using finite volume method for a wide range of inlet velocities. The average velocity on several horizontal and vertical sections were calculated and normalized with inlet velocities. These normalized velocities were studied to illustrate roughness effect on flow velocity distribution in rock fractures. The results show that, by increasing flow rate, the symmetry of velocity profile decreases and inclines to the smooth fracture surface. Moreover, by increasing flow rate, the arrangement of flow channels changes and lower normalized flow rates take place through large apertures.